(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper gives an overview of the current state of radio frequency identity (RFID) generation. Apart from a short introduction to the concepts of the technology, essential modern and envisaged fields of software, as well as advantages, and obstacles of use are discussed. Radio frequency identity (RFID) is a time-honored term that is used to describe a device that transmits the identification (inside the shape of a completely unique serial number) of an object or character wirelessly, using radio waves. It is grouped below the extensive class of automatic identification technologies. RFID is more and more used with biometric technology for safety. On this paper basic standard of RFID era alongside its kinds are mentioned.